Dampak Kebijakan PSBB terhadap Konsentrasi PM2.5 di Indonesia - Dariyanto, Erwin (Jurnal Kebijakan Ekonomi, 2022)
The aims of this study was to examine the impact of implementation of the Large-Scale Social Restriction or PSBB policy on the concentration of particulate matter 2.5 (PM2.5). The observation period lasted from September 1, 2019 to December 31, 2020 in five major cities in Indonesia, namely Jakarta, Bandung, Yogyakarta, Semarang, and Surabaya. The data was processed using the fixed effect least square dummy variable (LSDV) model to test the impact of the PSBB policy or restrictions on citizen mobility to reduce the spread of COVID-19 on PM2.5 concentrations. As a result, the PSBB policy had a very significant impact on the decline in PM2.5 to 1,210 μg/m3. When testing the impact of PSBB per level, of the 4 PSBB levels, PSBB level 3 significantly reduces PM2.5 concentrations. While PSBB level 1, PSBB level 2 and PSBB level 4 can have an impact on decreasing PM2.5 concentrations, but not significantly. We hope this research can contribute to policy makers as a consideration when making decisions related to air quality control in Indonesia. Further research can be done by looking at the variable number of vehicles, the firmness of the apparatus in imple menting the PSBB. Keyword: Air pollution, COVID-19, PM2.5, PSBB